Preparation of Biofuel from Palm Oil Catalyzed by Ammonium Molybdate in Homogeneous Phase - Sepehr Sadighi; Seyed Kamal Masoudian Targhi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
Producing transportation fuels from bio sources was of prime importance due to the strict environmental legislations for producing clean fuels from conventional oil resources. However, the economical impacts of the biofuel production should be considered. In this study, the production of bio-naphtha and biodiesel from palm oil using homogeneous catalyst, i.e. an aqueous phase of ammonium molybdate, was studied. This catalyst was prepared by dissolving sodium molybdate in de-ionized water with hydrochloric acid, and then neutralizing the mixture with ammonium hydroxide. The solution was dried at 90 °C for 24 h to obtain ammonium molybdate. Then, characterization of the catalyst was done by informative techniques, such as XRD and FT-IR. The results showed that the main phase of the synthesized catalyst was molybdate ammonium hydrates (4MoO3.2NH3.H2O), and also bands of Mo–O, Mo–O–Mo, N–H and surface hydroxyl groups were observed in the sample. Moreover, activity test confirms that the bio-naphtha produced from the proposed method has a few aromatic components, and its sulfur content was negligible. Moreover, ash, nitrogen, sulfur and carbon residue were not detected in the produced biodiesel, and its Cetane index was 66.3. Therefore, it was a suitable fuel for diesel engines vehicles.